An Analysis of Filling Completeness and Return Punctuality of Inpatient Medical Record Document at Hospital - Rahayu, Yessi; Dewi, Oktavia; Herniwanti, Herniwanti; Rahayu, Endang P; Abidin, Aldiga Rienarti (JURNAL PROTEKSI KESEHATAN, 2024)
The completeness of the form, accuracy, accuracy of the records, and timeliness of returns are indicators of quality medical records and have not yet been achieved. This research aims to obtain information about the completeness of filling in and the timeliness of returning inpatient medical records at Bina Kasih Hospital Pekanbaru. This type of research is qualitative, with a case study approach, with thematic analysis by conducting interviews with 6 informants, conducting observations, and reviewing documents. It was found that the results of the input mechanism were that the high workload caused the open assessment of medical records to not be carried out properly, the skills of the staff were in line with the job description, the forms still used paper on patient status, this affected the incompleteness of filling in medical records, the filling method was carried out after an action had been taken on the patient. weak control and no sanctions for those who are not disciplined, in the aspect of the process of filling out the equipment in stages, the level of indiscipline is high. The output has not produced the expected results with a value of 60%, this result is below the hospital's minimum standard value of 80%.